Synthesis and antioxidant studies of novel bi-, tri-, and tetrapodal 9-aryl-1, 8-dioxo-octahydroxanthenes. Issue 11 (11th March 2015) - Iniyavan, P.; Sarveswari, S.; Vijayakumar, V.
Graphical abstract: Abstract: Compounds bearing two, three, and four 9-aryl-1, 8-dioxo-octahydroxanthenes units were synthesized by regioselective O-alkylation of monopodal xanthenes with bis-, tris-, and tetrakis(bromomethyl)benzenes as alkylating agents using K2 CO3 as base and DMF as solvent in moderate temperature. All the synthesized compounds were characterized by NMR and mass spectral data and then tested for antioxidant activity, as reflected by free radical scavenging, increased with increasing number of xanthene units.